COMPREHENSIVE ANALYSIS ON BIOAVAILABILITY AND BIOEQUIVALENCE STUDIES - 1Sultan Ali Almutairi, 2Abdulmohsen Musaad Almutairi, 3Fahad Owaidh Ali Almutairi, 4Ali Bunydir Almutairi, 5Abdullah Abdulrahman Almutairi, 6Alhumaidi FaihanAlmotairi, 7Mohammed Hamoud Almutair, 8Fawaz Yousef Almutairi (Chelonian Research Foundation, 2022)
Bioavailability and bioequivalence play a critical role within the pharmaceutical industry and provide imperative data concerning the execution of pharmaceutical items. This comprehensive audit investigates the concepts of bioavailability and bioequivalence, their significance in drug development, and strategies to assess them. An extensive literature audit investigates key ponders and propels within the field and highlights issues and needs related to bioavailability and bioequivalence. The plan, information investigation, translation strategies, and strategies for directing these considerations are discussed. The discoveries of chosen considerations are displayed through charts, tables, and charts, which appear as patterns in bioavailability and bioequivalence estimations. The discourse incorporates a basic assessment of the discoveries, methodological contemplations, and suggestions for execution and administration choices. In outline, proposals are given to move forward with the plan and conduct of bioavailability and bioequivalence considerations, to fathom current issues, and to extend inquiries about vital regions of investigation medicine. Keywords: Bioavailability, Bioequivalence, Pharmacokinetics, drug Development, Pharmaceutical Science